2016
DOI: 10.1016/j.ejmech.2016.03.064
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of Minor Groove Binders as anti- Trypanosoma brucei brucei therapeutics

Abstract: A series of 32 structurally diverse MGBs, derived from the natural product distamycin, was evaluated for activity against Trypanosoma brucei brucei. Four compounds have been found to possess significant activity, in the nanomolar range, and represent hits for further optimisation towards novel treatments for Human and Animal African Trypanosomiases. Moreover, SAR indicates that the head group linking moiety is a significant modulator of biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…The intrinsic fluorescence of some S-MGBs makes it possible to investigate their intracellular distribution in trypanosomes following incubation. As previously shown for T. b. brucei(21), experiments with the highly fluorescent 9 confirmed internalisation in T. congolense(Fig. 3a).…”
supporting
confidence: 83%
“…The intrinsic fluorescence of some S-MGBs makes it possible to investigate their intracellular distribution in trypanosomes following incubation. As previously shown for T. b. brucei(21), experiments with the highly fluorescent 9 confirmed internalisation in T. congolense(Fig. 3a).…”
supporting
confidence: 83%
“…By manipulating these variables potent antibacterial compounds have been discovered, one of which has completed phase 1 clinical trials, 17 and other compounds have been shown to be active against Trypanosoma both in cell-based studies and in mouse models of disease and leishmaniasis (unpublished results). 18,19 A potential benefit of targeting DNA is that it is to be expected that several binding sites will be occupied by S-MGBs leading to multiple mechanisms of action, which in turn could mitigate risks of rapid development of resistance. A counter balancing risk is that the ubiquity of DNA makes species selectivity critical.…”
Section: Ar T Ic Le In Fomentioning
confidence: 99%
“…For example, the clogD7.4 values for the set range between -3.28 and 6.97 (Table 1). 19 Compound inhibitory activity was determined in IC50 dose response format against Pf3D7 (chloroquine sensitive) and PfDd2 (chloroquine resistant) stains using a previously described high content imaging assay. 22 In addition, compounds were simultaneously tested for general cytotoxicity against HEK293 cells using an AlamarBlue based assay which measures cell metabolic activity.…”
Section: Ar T Ic Le In Fomentioning
confidence: 99%
“…46 This compound was built from Nmethylpyrrole amino acid amides and has an amidine end group (Scheme 1). Also, we modified a number of the fragments of the original structure.…”
Section: Scheme 6 Synthesis Of C-isopropyl-substituted Thiazole Amidmentioning
confidence: 99%